Private equity challenge - sprouts farmers market`s leveraged buyout - Costa, Francisco Machado Pinto Machado (2022)
This Investment Committee paper consists of a proposal for a potential Leveraged Buy out of Sprouts Farmers Market, a US-based specialty retailer focused on the organic food segment. The group developed a complete paper, including the creation of an investment thesis and business model, sustained on a previous market and company research, a concrete valuation and deal structuring, and an overview o fpossible exit strategies. This paper is an individual component that provides a thorough analysis of the company ́sdynamicsandhistoricalfinancials